Clinical association between non‐alcoholic fatty liver disease and the development of hypertension. Issue 11 (November 2014) - Ryoo, Jae‐Hong; Suh, Young Ju; Shin, Ho Cheol; Cho, Yong Kyun; Choi, Joong‐Myung; Park, Sung Keun
Abstract Background and Aim Non‐alcoholic fatty liver disease (NAFLD) is getting an increasing attention for its clinical implications on cardiovascular disease (CVD). However, epidemiologic data are not so evident to sustain the causative association between NAFLD and hypertension, the major cause of CVD. Accordingly, we designed this study to investigate the clinical association between NAFLD and the development of hypertension. Methods To assess the natural course of blood pressure according to degree of NAFLD (normal, mild, and moderate to severe), we conducted a prospective cohort study on the 22 090 Korean men without hypertension for 5 years. We serially checked the various metabolic factors including systolic and diastolic blood pressure in order to monitor the development of hypertension. Results The incidence rate of hypertension increased according to the degree of NAFLD (normal: 14.4%, mild: 21.8%, moderate to severe: 30.1%, P < 0.001). Even after adjusting for other multiple covariates, the hazard ratios (95% confidence intervals) for hypertension were higher in the mild group (1.07; 1.00–1.15) and moderate to severe group (1.14; 1.00–1.30), compared with normal group, respectively (P for trend < 0.001). Conclusion Development of hypertension is more potentially associated with the more progressive NAFLD than normal or milder state. In addition, NAFLD was an independent risk factor for hypertension.